Selected Decisions and Selected Documents of the International Monetary Fund, 32nd Issue. (Selected Decisions; Thirty-Second Issue, 2007, 2008)
Includes decisions, interpretations, and resolutions of the Executive Board and the Board of Governors of the International Monetary Fund, as well selected documents, to which frequent reference is made in the current activities of the Fund. In addition, it includes certain documents relating to the Fund, the United States, and other international organizations;.